Legal regulations governing livestock production relevant to the integration of Hungary into the EU - Szabó, Gábor; Bene, D.; Varga, P. (Acta Agraria Kaposváriensis, 1999)
This study provides an outline of the acts and directives relevant to livestock production, from the aspects of environmental conservation (nature conservation) and the protection of animals. The first part of the study gives a brief overview of the environmental conservation-related aspects of the acts on livestock production and on animal health and hygiene, and also on the manufacture and marketing of animal feeds. In the second part the Act on the Protection of Animals and the associated directives are outlined. Lastly, the authors refer to the government directive relating to the safeguarding of protected animal species, the legal base for which was provided by the 1996 Act on Nature Conservation. This overview of the above laws leads to the conclusion that viewed from the aspect of legislation, there is no obstacle to the integration of Hungarian livestock production into that of the European Union.
Keywords: European Union; integration; livestock production; environmental conservation; protection of animals